ADAPTIVE SOFTWARE DEVELOPMENT SEBAGAI MODEL PENGEMBANGAN APLIKASI LELANG KARET - Andri, Andri; Suyanto, Suyanto (Universitas Hamzanwadi, 2020)
Rubber auction cooperatives are cooperatives whose main function is to auction rubber agricultural products for these member communities. Currently, among the problems that exist in the auction process, namely: first, auction entrants must come to the auction site even if only to bid a price. Second, the auction administration process has redundant of entrant data due to having to fill out a form every time they participate in the auction. From these two problems, this research will conduct application development as an auction medium for related parties. The application developed is a mobile-based application so that it can be accessed easily by all parties. The method used in the development process is the adaptive software-development method with three major stages of speculation, collaboration, and learning which was tested using black box testing.Â The Research Results are an application with the main feature of conducting the auction process from the cooperative's side, and auction participants can bid prices through the application. The application developed also functions properly in accordance with existing features as evidenced by the results of application testing using the black box technique so that it can help the rubber auction process for related parties.